Integration of Geospatial Technologies in Geology: Opening New Economic Horizons - Alimova D.B.; Khudayarov B.A.; Nazarov X.; Komilova K.; Turaev F.; Yusupov E. (E3S Web of Conferences)
This article examines the impact of technological innovation on the geological sphere and its impact on economic processes. The study analyzed articles published in recent years on the impact of technological innovation on the geological industry and its impact on the economy. Geographic information systems have been found to play a critical role in geological activities. The study confirmed that the use of geographic information systems reduces the time and costs of geological research, and also increases the accuracy of the data obtained. In addition, another significant aspect of digitalization of the geological industry was studied, namely the use of Earth remote sensing methods. The introduction of digital technologies into the geological field has been shown to bring significant economic benefits. The Koraozek and Tebinbulak iron ore deposits in the Republic of Karakalpakstan are shown using remote sensing techniques. In general, the use of remote sensing of the Earth is a powerful tool for geological research, providing geologists with access to extensive and accurate information about the state of the Earth’s surface and its resources. This method plays an important role in modern geology, contributing to a more effective and accurate study of our planet and its resources.